2019
DOI: 10.7554/elife.49187
|View full text |Cite
|
Sign up to set email alerts
|

Identification of TMEM206 proteins as pore of PAORAC/ASOR acid-sensitive chloride channels

Abstract: Acid-sensing ion channels have important functions in physiology and pathology, but the molecular composition of acid-activated chloride channels had remained unclear. We now used a genome-wide siRNA screen to molecularly identify the widely expressed acid-sensitive outwardly-rectifying anion channel PAORAC/ASOR. ASOR is formed by TMEM206 proteins which display two transmembrane domains (TMs) and are expressed at the plasma membrane. Ion permeation-changing mutations along the length of TM2 and at the end of T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
154
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(171 citation statements)
references
References 59 publications
17
154
0
Order By: Relevance
“…A previous study has reported that the TMEM family is widely expressed in mammalian cells (39), which is in accordance with the present study. In the present study, the results of the expression profiling analysis demonstrated that TMEM206 expression was significantly increased in colorectal cancer, breast cancer, lymphoma and liver cancer, and reduced in the kidney cancer datasets.…”
Section: Discussionsupporting
confidence: 94%
“…A previous study has reported that the TMEM family is widely expressed in mammalian cells (39), which is in accordance with the present study. In the present study, the results of the expression profiling analysis demonstrated that TMEM206 expression was significantly increased in colorectal cancer, breast cancer, lymphoma and liver cancer, and reduced in the kidney cancer datasets.…”
Section: Discussionsupporting
confidence: 94%
“…activated Cl − channel (PAC or PACC1, Fig. 1A), in two independent screens (Ullrich et al, 2019;Yang et al, 2019a). PAC is involved in acid-induced neuronal cell death and PACknockout mice are partially protected from ischemic brain injury (Yang et al, 2019a).…”
Section: Acidosismentioning
confidence: 99%
“…Identifying and characterizing these channels has relied heavily on fluorescent chloride reporters. In many cases, screens using genetically encoded halide-sensitive yellow fluorescent protein (YFP) variants have identified the chloride channel involved in a given physiological process (Ullrich et al, 2019;Voss et al, 2014, Qiu et al, 2014Yang et al, 2019a). However, diverse physiological roles for chloride necessitate reporters that can provide information in various contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies on the ion channel properties of human PAC with point mutations and fish PAC suggested that PAC directly forms the proton-activated Cl − channel pore [6]. Using a very similar approach, another independent study also identified PAC (TMEM206) as the proton-activated Cl − channel [7].…”
Section: Introductionmentioning
confidence: 95%